Social Mechanisms in Local Transformations: Towards a Conclusion. Issue 4 (30th March 2015) - Faist, Thomas
Abstract: The contributions assembled here can be grouped under three main issues and the respective questions associated with them. They offer, first, answers to questions concerning the context, the dynamics, and the consequences of transnational linkages on the local level respectively. First, what is the context created by the large‐scale transformations for local‐level development and inequalities? Here, trends captured by terms such as neo‐liberalism come to mind. Second, how do transnational practices work with respect to the local level? This question implies an inquiry into the roles played by migrants and other agents for creating, sustaining, and changing ties across national states' borders. Third, what are the consequences of transformation for the transnational maze of ties across localities for actors' identities and for social inequalities between groups? This question is of particular interest because the diversification of social life mentioned in the preceding texts becomes so visible at the local level. The following conclusions address each of these three questions and identify the main social mechanisms underlying the concomitant social processes. Copyright © 2015 John Wiley & Sons, Ltd.